Financial Literacy and Financial Coping Strategy During Covid-19 Pandemic in West Sumatra - Verni Juita (Ekonomis: Journal of Economics and Business, 2022)
The Covid-19 pandemic has affected health conditions and the living standard of many families in Indonesia, including in West Sumatra. This study aims to analyse how the financial literacy possessed by each individual family members helps their financial conditions to be able to mitigate and survive from the adverse economic effects caused by the public health crisis, including choosing the best coping strategies. To attain those objectives, we conduct an online survey using a structured questionnaire and a convenience sampling method to 229 respondents aged over 17 years old living in each regions in West Sumatra. Using a simple descriptive statistical analysis, the results show that the impact of Covid-19 crisis is more substantial for individuals with lower financial literacy, especially related to financial obligations and resilience to long-term financial liabilities. However, it turns out that there are no differences in the survival strategies adopted by groups of individuals with different levels of financial literacy.